The Role Of Parents In The Moral Education Of Children Of Primary School Age - Muhammad Feri; Sutrisno Sutrisno (POTENSIA: Jurnal Kependidikan Islam, 2022)
Morals are very important in humans as the most perfect creatures that God created. One who has a role in moral education is parents. This study aims to determine the role of parents in the moral education of elementary school age children. The approach used is a qualitative case study method with interviews with 6 parents to collect data. The results obtained are that most parents have played their role in the moral education of elementary school age children. The roles that emerge are parents as mentors, role models, protectors, supervisors and friends for their children. Parents are also educators who instill religious values in their children. However, there are still parents who forget their responsibilities in the moral education of their children. The role of parents is needed in elementary school moral education so that the formation of children who have noble character.